Psychosocial Competencies and Risky Behaviours in Peru - Marta Favara; Alan Sanchez (Institute for the Study of Labor (IZA), 2016)
We use a unique longitudinal dataset from Peru to investigate the relationship between psychosocial competencies related to the concepts of self-esteem, self-efficacy, and aspirations, and a number of risky behaviours at a crucial transition period between adolescence and early adulthood. First of all, we document a high prevalence of risky behaviours with 1 out of 2 individuals engaging in at least one risky activity by the age 19 with a dramatic increase between age 15 and 19. Second, we find a pronounced pro-male bias and some differences by area of residence particularly in drinking habits which are more prevalent in urban areas. Third, we find a negative correlation between early self-esteem and later risky behaviours which is robust to a number of specifications. Further, aspiring to higher education at the age of 15 is correlated to a lower probability of drinking and of engaging in criminal behaviours at the age of 19. Similarly, aspirations protect girls from risky sexual behaviours.
Keywords: I12; K42; 330; risky behaviours; psychosocial competencies; Peru; young lives